The 1957 Domestic Loan and the Completion of the Era of “Voluntary-Obligatory Loans” (Middle Ural) - V. N. Mamyachenkov; E. A. Ivanov; V. V. Shvedov (Научный диалог, 2020)
The purpose of this article is to investigate events related to a significant fact in the economic history of the USSR - the actual refusal by the state of its obligations on previously placed domestic loans in 1957. The relevance of the study is due to the interest shown in researching the experience of overcoming the financial crisis. The scientific novelty of the study is seen in the fact that archival materials not previously published are introduced into the scientific circulation. It is stated that from the point of view of the modern economy, government borrowing is an indispensable and mandatory attribute of public finances. It is stated that the reason for the need for such borrowing lies in the property of a loan to reduce the time of realization of personal and social needs. It focuses on the fact that the culmination and final moment of the era of permanent state internal borrowing was the factual default of the state declared in the spring of 1957. A review of the statements of citizens characterizing their attitude to this event is carried out. It is proved that the default did not have a significant impact on the state of the family budgets of citizens of the country. It is concluded that in the history of the Soviet Union the mentioned event will remain an event of the passive-palliative type.